Outcomes Among Clopidogrel, Prasugrel, and Ticagrelor in ST-Elevation Myocardial Infarction Patients Who Underwent Primary Percutaneous Coronary Intervention From the TOTAL Trial - Welsh, Robert C; Sidhu, Robinder S; Cairns, John A; Lavi, Shahar; Kedev Sasko; Moreno, Raul; Cantor, Warren J; Stankovic, Goran; Meeks, Brandi; Yuan, Fei; Džavík, Vladimír; Jolly, Sanjit S (Elsevier BV, 2019)
Robust comparisons between oral P2Y12 inhibitors (clopidogrel, prasugrel, ticagrelor) in ST-elevation myocardial infarction (STEMI) patients who undergo primary percutaneous coronary intervention are lacking. We sought to evaluate outcomes on the basis of P2Y12 inhibitor therapy in patients from the Thrombectomy With PCI Versus PCI Alone in Patients With STEMI Undergoing Primary PCI (TOTAL) trial.